Previdência e reposiç\~ao no serviço público civil federal do poder executivo: Microssimulaç\~oes - Bernardo Patta Schettini; Gustavo M. V. Pires; Cláudio H. dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper analyzes the personnel expenditures in the Brazilian federal civil public service using administrative records from the Executive Branch. There are two contributions which are noteworthy because they may improve the understanding of policy makers regarding the evolution of those expenses in the upcoming years. First, we undertake simulations in order to assess the effects of the Proposal for Constitutional Amendment no 287. It should be noted that this exercise disregards that the federal govern will have to replace, to some extent, those people who are leaving the public service. Hence, in what follows, we formulate replacement scenarios to try and gauge the cost of different hiring strategies. Furthermore, we report the robustness of some results with respect to specific assumptions. In a nutshell, the results indicated that the reform will bring about economies for the public coffers over the next years, mainly due to the fall in the value of the survivors' pensions. Nonetheless, given the enormous amount of people that will become eligible for retirement, the replacement policy to be followed by the government has a substantial weight on the size the payroll will reach.
Keywords: E66; H55; H68; M54; 330; personnel expenditures; federal civil public service; microsimulations; pension reform; replacement